Efficient optimization methodology for laser powder bed fusion parameters to manufacture dense and mechanically sound parts validated on AlSi12 alloy. (1st February 2021) - Gheysen, Julie; Marteleur, Matthieu; van der Rest, Camille; Simar, Aude
Abstract: The main drawback of laser powder bed fusion (L-PBF), commonly called selective laser melting (SLM) is the high porosity which may lead to an early failure of the parts. To minimize it, the L-PBF parameters need to be optimized focusing on the laser power, scanning speed and hatching space. However, no standard guideline exists. In this study, an efficient and cost-effective methodology is developed and validated on AlSi12. This innovative methodology brings together single scan tracks (SST), macroscopic properties analysis and design of experiments (DOE). It requires three batches of SST, cubes and tensile samples. The DOE significantly decreases the manufacturing and characterization costs. 9 SST are sufficient to identify a process window that is 85% similar to the one obtained from a full factorial design with 105 SST. This process window reliably leads to high densities and better mechanical properties in comparison to the state-of-the-art properties reported in the literature for L-PBF AlSi12. In conclusion, a methodology using only 9 SST, 18 cubes and 12 tensile tests has been validated on AlSi12. It is further envisioned to optimize the L-PBF parameters of any existing or new alloy leading potentially towards better mechanical properties than the state-of-the-art in the literature. Graphical abstract: Unlabelled Image Highlights: The optimum L-PBF parameters have been established for AlSi12 based on an efficient and cost-effective methodology. The methodology only requires 9 single scan tracks (SST), 18 cubes and 12 tensile samples to optimize the L-PBF parameters. 9 SST identifies a process window 85% similar to the one resulting from a full factorial design with 105 SST. The process window obtained based on the 9 SST leads to high-density (> 99.3%), proving the relevance of the SST. The optimum L-PBF parameters lead to better static mechanical properties than the state-of-the-art ones reported in literature for L-PBF AlSi12.